2023
DOI: 10.18240/ijo.2023.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes in the macular area in diabetic macular edema after a single intravitreal injection of aflibercept

Abstract: AIM: To evaluate the changes in macular morphology and function after a single intravitreal injection of aflibercept in diabetic macular edema (DME) using optical coherence tomography angiography (OCTA) and MP-3 microperimetry. METHODS: Twenty-eight patients (42 eyes) diagnosed with DME were treated with intravitreal injection of aflibercept. The changes in best corrected visual acuity (BCVA), central retinal thickness (CRT), foveal avascular zone (FAZ) area, vessel density of superficial retinal capillary ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Malagola et al [29] reported that after intravitreal injection of aflibercept to treat DME (observation time points were 3-25mo), there was no significant change in retinal microvascular density. The results of Zhang et al [30] showed that the FAZ area and retinal capillary density may not change significantly in the short term after receiving anti-VEGF therapy. In our study, there was no significant change in FAZ area in either the combination therapy group or the aflibercept group, which is consistent with the results of the above studies.…”
Section: Resultsmentioning
confidence: 98%
“…Malagola et al [29] reported that after intravitreal injection of aflibercept to treat DME (observation time points were 3-25mo), there was no significant change in retinal microvascular density. The results of Zhang et al [30] showed that the FAZ area and retinal capillary density may not change significantly in the short term after receiving anti-VEGF therapy. In our study, there was no significant change in FAZ area in either the combination therapy group or the aflibercept group, which is consistent with the results of the above studies.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the growing number of annual citations also re ects the growing in uence of related publications. On the one hand, this growth trend is due to the endless stream of DME treatment methods: including ranibizumab, bevacizumab, a ibercept, dexamethasone and other medicine [34][35][36] ; on the other hand, it is due to the gradual increase in the evaluation methods of the therapeutic effect of diabetic macular edema, such as optical correlation tomography angiography [37,38] . The year 2020 witnessed the largest published number on the treatment of DME throughout the past decade, which may be related to the ranibizumab's patent expired in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DR-associated retinal neurodegeneration might occur before any detectable microcirculatory abnormalities in ophthalmic examinations [9] . Microperimetry offers a possibility to record assessment of retinal sensitivity and the location and stability of fixation [10][11] . It has been reported that retinal sensitivities are decreased compared to control subjects in type 2 diabetes patients without DME [12] .…”
Section: Introdutionmentioning
confidence: 99%